Skills development for value chain actors in African agriculture - Kirui, Oliver K. (International Food Policy Research Institute, 2020)
This chapter highlights policies and interventions related to skills development and training for agricultural and food value chain development in Africa. The opening section provides the background and context for the study. The section that follows is dedicated to describing skills gaps and the training needs of various agrifood value chain actors in Africa. The next section describes skills development and training provision for agrifood value chain actors. It provides an overview of continental policies and interventions that characterize skills development for agricultural value chain actors, discusses some examples of significant agricultural technical and vocational education and training (ATVET) initiatives in selected countries in Africa, mulls participation of the private sector in skills development and training, and discusses the prospects of a “dual system” of skills development in African agriculture. The final section concludes the chapter with a summary of main findings and some policy implications.